Gen Z Consumer Behavior in Consuming Local Products in the Era of Digital Hyperreality - Rinaldi Bursan (International Forum of Researchers and Lecturers, 2025)
This research explores the symbolic consumption patterns of Generation Z in engaging with local products during the digital hyperreality era, emphasizing the roles of ethical consumption, hyperreality values, and digital identity in shaping purchase intentions. Using a quantitative design through PLS-SEM complemented by qualitative evidence, the study shows that both ethical consumption and hyperreality significantly shape digital identity (β = 0.42; β = 0.53, p < 0.001). Digital identity strongly drives purchase intention (β = 0.65, p < 0.001), while ethical consumption does not directly affect it. Mediation analysis demonstrates that digital identity fully mediates the relationship between ethical consumption and purchase intention, and partially mediates the impact of hyperreality. Qualitative findings highlight that Gen Z’s buying decisions are influenced by symbols and imagery showcased on social media, where ethical aspects only become relevant when they align with digital aesthetics. These results strengthen the postmodernist perspective that consumption in the digital era is primarily about signs, images, and symbols that go beyond mere utility. The study suggests that MSMEs should strategically embed symbolic narratives, ethical dimensions, and visual aesthetics into digital marketing to appeal to Gen Z while promoting sustainability.